Określanie wieku młodych brzóz Betula pendula Roth rosnących na gruntach porolnych - Tkaczyk, Miłosz; Tomusiak, Robert (Leśne Prace Badawcze, 2013)
In Poland, according to the law (amendment of the act of 21st May 2010) – on the provision of information on the environment and its protection, public participation in environmental protection and environmental impact assessments etc. (Official Law Journal article 08.199.1227, as amended) – the owner can cut down trees without permission, if they do not exceed the age of 10 years old. However, if an owner happens to cuts down a tree on his property without knowing the age of the tree, he is liable to prosecution under this act. The aim of this study is to verify whether there is a possibility to calculate the actual age of silver birch trees growing on former agricultural lands using features that enable age of standing trees to be identified. Using these criteria, owners would be able to calculate the age of trees on their own. The research used 183 sample trees located on three research plots. For each tree, the dbh, height and prepared samples of wood from the trees base were used to give the age of the tree. The relationship between age and dbh, as well as between the age and the height was examined. The strength of correlation was compared and the strongest was used in the proposed model. Using these correlations two types of charts were constructed to estimate the age of young birches on the basis of dbh and height.